Oral health status and treatment need among institutionalized elderly in India - S Sabiha Shaheen; Suhas Kulkarni; Dolar Doshi; Srikanth Reddy; Padma Reddy (Wolters Kluwer Medknow Publications, 2015)
Aim: To assess the oral health status and treatment needs among elderly people aged 60 years and above residing as inmates in the old age homes of Hyderabad and Secunderabad, Andhra Pradesh, India. Settings and Design: A cross-sectional study was performed to determine the oral health status and treatment needs among elderly people. Materials and Methods: In order to assess the oral health status and treatment needs, the clinical assessment of oral mucosa, community periodontal index, loss of attachment, dentition status and treatment need, prosthetic status and prosthetic need was recorded based on a modified World Health Organization 1997 proforma. Statistical Analysis Used: Multi-group analysis was done using analysis of variance. P < 0.05 was considered statistically significant. Results: Of the 812 inmates, 431 (64.0%) of the study participants had oral mucosal lesions. In terms of periodontal status, all sextants were excluded (Code "X") in 324 (39.9%) subjects. Out of dentate population, a majority of the inmates (219; 27.0%) presented with deep pockets (Code "4") followed by shallow pockets (Code "3" - 183; 22.5%). The majority of the subjects had no prosthesis in the upper arch (85.0%) and lower arch (86.6%). Conclusion: The study demonstrated poor oral health among institutionalized elderly inmates. Oral mucosal lesions were found to be higher and periodontal status was also poor amongst the study population.